2016
DOI: 10.1128/aac.00683-16
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label Study of Absorption and Clearance of 1% Voriconazole Eye Drops

Abstract: h Twenty participants undergoing elective cataract surgery received 1% voriconazole eye drops (1 drop per eye) either 20, 40, 60, or 80 min before surgery. Median voriconazole concentrations of 1.9 to 3.2 mg/liter in aqueous humor samples were attained over the first 80 min, which were higher than in vitro MIC 90 values for typical fungi that cause keratitis. Fungal keratitis remains one of the most difficult-to-treat corneal infections and accounts for approximately 50% of infectious keratitis cases in develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…14 Although there are still no topical voriconazole agents, 1% or 2% voriconazole, which is prepared by mixing voriconazole powder and sterile water, has been proven effective and safe in the treatment of fungal keratitis. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…14 Although there are still no topical voriconazole agents, 1% or 2% voriconazole, which is prepared by mixing voriconazole powder and sterile water, has been proven effective and safe in the treatment of fungal keratitis. 15,16…”
Section: Introductionmentioning
confidence: 99%
“…20 Accordingly, corneal voriconazole concentrations were found to be equivalent, after a regimen of eye drops every 2 h, to that in the aqueous humour of humans, 20 and elevated aqueous humour concentrations were rapidly obtained after eye instillation in humans. 18 In topically treated rats, plasma concentrations were close to those in healthy horses 21 and presumably lower than those associated with adverse side effects in humans. 22 Owing to ethical constraints, one eye of each rat was infected.…”
Section: Discussionmentioning
confidence: 77%
“…In an AK rat model, topical and oral voriconazole doses were determined according to previous studies in humans. 18 Eye-drop treatment from day 7 p.i. reduced AK lesion worsening from day 7 to day 14 p.i.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Topically administered 1% voriconazole eye drops have been documented to achieve good intraocular penetration in non-inflamed and inflamed eyes. [ 23 26 27 28 ] It is evident from these studies that 1% voriconazole eye drops offered sufficient voriconazole concentrations in the aqueous humor which is above the MIC 90 (0.06 – 8 mg/L) for most fungal species. [ 29 ] However, a large filamentous fungal susceptibility study using ocular isolates from keratitis cases in South India showed that MIC 90 of voriconazole for the Fusarium isolates were in the range of 0.13 to >64 mg/ml as compared to natamycin whereas the in vitro activity of voriconazole against A. flavus isolates were in the range of 0.13 -8 mg/ml.…”
Section: Discussionmentioning
confidence: 99%